Factors Affecting Gold Price Prediction and the Use of Deep Learning Techniques for Gold Price Prediction - Laor Boongasame (Advances in finance, accounting, and economics book series, 2022)
“Gold” is a term that refers to a collection of precious metals. Gold's bright, shiny yellow color is its defining characteristic. Due to the availability of sophisticated computational techniques such as generalized auto-regressive conditional heteroskedasticity (GARCH), it is possible to perform a more accurate analysis of gold price expression data using deep learning. In this chapter, techniques for predicting the gold price using deep learning are presented. Also talked about were problems that have come up in the field and possible directions for future work.
Keywords: Stock Market Forecasting Methods; Market Dynamics and Volatility; Currency Recognition and Detection